A feedforward relationship between active Rac1 and phosphorylated Bcl-2 is critical for sustaining Bcl-2 phosphorylation and promoting cancer progression. (10th August 2019) - Chong, Stephen Jun Fei; Lai, Jolin Xiao Hui; Qu, Jianhua; Hirpara, Jayshree; Kang, Jia; Swaminathan, Kunchithapadam; Loh, Thomas; Kumar, Ansu; Vali, Shireen; Abbasi, Taher; Pervaiz, Shazib
Abstract: Active GTPase-Rac1 is associated with cellular processes involved in carcinogenesis and expression of Bcl-2 endows cells with the ability to evade apoptosis. Here we provide evidence that active Rac1 and Bcl-2 work in a positive feedforward loop to promote sustained phosphorylation of Bcl-2 at serine-70 (S70pBcl-2), which stabilizes its anti-apoptotic activity. Pharmacological and genetic inactivation of Rac1 prevent interaction with Bcl-2 and reduce S70pBcl-2. Similarly, BH3-mimetic inhibitors of Bcl-2 could disrupt Rac1-Bcl-2 interaction and reduce S70pBcl-2. This effect of active Rac1 could also be rescued by scavengers of intracellular superoxide (O2 .− ), thus implicating NOX-activating activity of Rac1 in promoting S70pBcl-2. Moreover, active Rac1-mediated redox-dependent S70pBcl-2 involves the inhibition of phosphatase PP2A holoenzyme assembly. Sustained S70pBcl-2 in turn secures Rac1/Bcl-2 interaction. Importantly, inhibiting Rac1 activity, scavenging O2 .− or employing BH3-mimetic inhibitor significantly reduced S70pBcl-2-mediated survival in cancer cells. Notably, Rac1 expression, and its interaction with Bcl-2, positively correlate with S70pBcl-2 levels in patient-derived lymphoma tissues and with advanced stage lymphoma and melanoma. Together, we provide evidence of a positive feedforward loop involving active Rac1, S70pBcl-2 and PP2A, which could have potential diagnostic, prognostic and therapeutic implications. Highlights: Rac1 and Bcl-2 work in a positive loop to sustain Bcl-2 phosphorylation at Ser-70. Active Rac1 binds to Bcl-2 for redox-mediated inhibition of PP2A assembly. Inhibition of PP2A assembly induces accumulation of phosphorylated Bcl-2. Phosphorylated Bcl-2 further secures Rac1/Bcl-2 interaction. The positive loop is significantly prominent in severe stages of patient lymphomas.